Multi-domain field-test battery for performance profiling and inter-limb asymmetry screening in competitive Sanda Wushu - Novita; Lei Ying; Wan Ahmad Jaafar Wan Yahaya; Tansa Trisna Astono Putri (Journal of Coaching and Sports Science, 2026)
Background: Despite the complex physiological, technical, and mechanical demands of Sanda Wushu, athlete monitoring still relies largely on subjective coach observation and self-report. A feasible, objective, and coach-interpretable field-testing framework is therefore needed to detect performance changes and inter-limb asymmetry before integrating more complex wearable-sensor technologies. Aims: To examine the feasibility, responsiveness, and descriptive asymmetry-monitoring value of a standardized multi-domain field-test battery administered across a full training squad of Sanda Wushu athletes. Methods: An observational, field-based, repeated-measures monitoring study involved 72 nationally competing athletes (36 males and 36 females; age 18–30 years, M = 24.2, SD = 3.7). The battery was administered in July (Session 1) and October 2025 (Session 2). Valid results were benchmark-normalized to a composite Performance Index (PerfIndex, 0–1 scale; higher = better) and a categorical Score Index (ScoreIndex, 1–5 ordinal scale; higher = better). Inter-limb asymmetry (%) was computed for SL Wall Sit and Triple Hop Jump. Paired t-tests were reported with 95% CIs, Cohen's dz, Hedges' g, and a sensitivity analysis excluding four athletes with block-missing Session 1 items. Results: PerfIndex increased significantly from 0.727 ± 0.031 to 0.755 ± 0.033, mean difference +0.029, 95% CI [0.024, 0.034], t(71) = 11.46, p < .001, dz = 1.35, Hedges' g = 1.34. ScoreIndex showed the same pattern (2.92 ± 0.25 to 3.16 ± 0.26; t(71) = 9.41, p < .001, dz = 1.11, Hedges' g = 1.10). SL Wall Sit asymmetry increased slightly but significantly (27.9% to 30.9%, p = .023, dz = 0.28); Triple Hop asymmetry did not change significantly (11.5% to 11.7%, p = .718). Asymmetry values above the descriptive 15% reference zone were observed in a substantial share of the squad at both sessions. Conclusion: The field-test monitoring framework was feasible for squad-level implementation and detected small-to-moderate improvements in composite performance across two sessions. Inter-limb asymmetry screening also identified athletes requiring further assessment, although the findings should be interpreted as monitoring signals rather than diagnostic indicators.